Impacto da reconciliação contábil nas demonstrações financeiras - Moino, Débora Borbon (2022)
Accounting Reconciliation is a process that aims to identify failures along a company's production and administrative chain that result in monetary errors that will affect the corporation's results and compliance. These failures can sensitize or tarnish the credibility of controls and information, as well as of its directors and the accountant, therefore, the reconciliation aims to ensure the correct accounting calculation based on safe and reliable values to generate reports, budgets, and timely decisions by its executives. The Accounting Reconciliation process suggests an interaction between the CFO and the accountant to certify the regularity of operations and Financial Statements. To seek the veracity of the numbers reported in the accounting calculations and management reports of the controllership, it is first necessary to go through a meticulous process of analysis of the accounting accounts, as well as the technical accounting team's knowledge of the existing operations linked to each component of the accounts of the company's Accounting Plan and, for this, it uses one of the main resources among its accounting activities: the so-called Accounting Reconciliation. The research aimed, through the analysis of the Case Study of a Human Resources company in the State of São Paulo, here called Alfa Company, to measure the impact on its reports that, due to the absence of the reconciliation process in the entity until the year of 2015 generated a distorted balance with non-existent credits and debits in the balance sheet accounts, in addition to the lack of visibility for the proper use of the financial cash flow, leading to the depletion of available cash and banks due to the use of the company's reserves. In 2016, the company sought to restructure its accounting and improve methods for controlling and identifying faults. Thus, its balance sheets and income statements for the periods 2012 to 2020 were analyzed and compared, reallocating to 2015 the adjustments identified in the 2016’s reconciliations, generating a different perspective with new impact projections for that year and the following years. As a result of the research, it is concluded that the Accounting Reconciliation process that occur in 2016 proved in practice the benefit of this activity, bringing in that year the focus on regularizing loss-making operations and the necessary visibility of accounting calculations, which are transformed into management reports, therefore, confirming its relevance in the company's management. The Financial Statements indicate that the entity took more one year to balance its accounts, and only in 2018 it managed to realize the financial return in accordance with the correct maintenance of available cash using the deferred tax benefits certified and reconciled in 2016, and this situation shows the temporal loss in company measures and actions. However, the significant improvement in the company's final numbers can be concluded after the restructuring and adjustments that took place in 2016, combined with the use of Accounting Reconciliation. Therefore, the contribution provided in this research was to alert about preventive and non-reactive accounting activities, with the partnership of a technically prepared accounting team, structured and attentive to the processes, resulting in administrative benefits for the company